The Impact of Employer Branding on Employee Performance with Organizational Commitment as a Mediating Variable : a Study of Employees at PT. Bank BRI Branch Office Pariaman - Kurnia Abdasni Marta; Harif Amali Rivai; Rahmi Fahmy (Jurnal Ekonomi Manajemen Sistem Informasi, 2025)
This study is motivated by the critical importance of strategic human resource management in addressing the increasingly complex competition within the banking sector. The primary objective of this research is to examine the influence of employer branding on employee performance, with organizational commitment acting as a mediating variable, at PT Bank Rakyat Indonesia (Persero) Tbk, Branch Office Pariaman. A quantitative approach was employed, utilizing a survey method involving marketing employees at the BRI Pariaman Branch. Data were analyzed using the Structural Equation Modeling–Partial Least Square (SEM–PLS) technique.The employer branding construct was measured through five key dimensions: interest value, social value, economic value, development value, and application value. Organizational commitment was assessed using three dimensions: affective, continuance, and normative commitment. Meanwhile, employee performance was evaluated based on quality, quantity, and timeliness indicators.The results revealed that employer branding has a direct and significant positive effect on employee performance. However, employer branding was found to have no significant positive effect on organizational commitment. Consequently, organizational commitment does not serve as a mediating variable in the relationship between employer branding and employee performance.From a practical standpoint, the findings suggest that BRI management should integrate the core values of employer branding into their human capital strategies, foster a collaborative work culture, and provide clear career development pathways. Theoretically, this study contributes to a deeper understanding of the relationship between employer branding, organizational commitment, and employee performance, particularly within the context of the financial services industry.